Comprehensive analysis of transcriptomic profiling of 5‐methylcytosin modification in placentas from preeclampsia and normotensive pregnancies. Issue 2 (24th January 2023) - Wei, Xiaohong; Zhou, Shengping; Liao, Lingyun; Liu, Min; Gao, Yijie; Yin, Yangxue; Xu, Qin; Zhou, Rong
Abstract: Increasing evidence suggests that RNA m5C modification and its regulators have been confirmed to be associated with the pathogenesis of many diseases. However, the distribution and biological functions of m5C in mRNAs of placental tissues remain unknown. we collected placentae from normotensive pregnancies (CTR) and preeclampsia patients (PE) to analyze the transcriptomic profiling of m5C RNA methylation through m5C RNA immunoprecipitation (UMI‐MeRIP‐Seq). we discovered that overall m5C methylation peaks were decreased in placental tissues from PE patients. And, 2844 aberrant m5C peaks were identified, of which respectively 1304 m5C peaks were upregulated and 1540 peaks were downregulated. The distribution of m5C peaks were mainly located in CDS (coding sequences) regions in placental tissues of both groups, but compared with the CTR group, the m5C peak in PE group before the stop code of CDS was significantly increased and even higher than the peak value after start code in CDS. Differentially methylated genes were mainly enriched in MAPK/cAMP signaling pathway. Moreover, the up‐regulated genes with hypermethylated modification were enriched in the processes of hypoxia, inflammation/immune response. Finally, through analyzing the mRNA expression levels of m5C RNA methylation regulators, we found only DNMT3B and TET3 were significantly upregulated in PE samples than in control group. And they are not only negatively correlated with each other, but also closely related to those differentially expressed genes modified by differential methylation.Our findings provide new insights regarding alterations of m5C RNA modification into the pathogenic mechanisms of PE.